The Effect of ROA, ROE, NPF, and FDR on the Share Price of BSI and Panin Dubai Syariah Bank in 2021 - 2024 - Faqih, Abdullah; Millah, Hayatul; Fajri, Ahmad (Jurnal Iqtisaduna, 2025)
This study aims to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR) on stock prices at Bank Syariah Indonesia (BSI) and Panin Dubai Syariah Bank during the period 2021–2024. This study uses a quantitative approach with multiple linear regression analysis methods. The study results show that, partially, ROA has a positive and significant effect on stock prices, while ROE has a negative and significant effect. NPF has no significant effect on stock prices, while FDR shows a negative and significant effect. Simultaneously, these four variables have a significant effect on stock prices. These findings indicate that financial performance indicators are essential in determining the value of Islamic banking stocks in Indonesia. This study is expected to be a consideration for investors in making investment decisions and for bank management in improving the company's financial performance.